دور الاستثمار في تكنولوجيا المعلومات الحديثة في تطويرالخدمات المصرفية - حسين تامه; نصر الدين ناصري; البخاري عقيب (university of eloued جامعة الوادي, 2025)
"الملخص: تهدف هذه الدراسة إلى إبراز دور الاستثمار في تكنولوجيا المعلومات الحديثة في تطوير الخدمات المصرفية، وذلك بدراسة ميدانية في بنك الفلاحة والتنمية الريفية وكالة الوادي، ومن أجل بلوغ هذا الهدف تم الاعتماد على المنهج الوصفي في الجانب النظري من الدراسة، حيث تطرقنا نظريا لتكنولوجيا المعلومات الحديثة وكذا الخدمات المصرفية، كما تم الاعتماد على المنهج التحليلي في دراسة الحالة حيث تم الاعتماد على المقابلة والاستبيان كأدوات رئيسية للدراسة، وتم توزيع الاستبيان على عينة من عملاء المؤسسة محل الدراسة حيث تم تحليل العينة باستخدام عدة أساليب إحصائية لاختبار فرضيات الدراسة وقد تم الوصول إلى مجموعة من النتائج:  يرى العملاء أن البنك يستخدم التكنولوجيا الحديثة بدرجة متوسطة إلى كبيرة (33.3 %).  أكدت غالبية آراء العينة على وجود مجال للتحسين فيما يتعلق بسرعة انجاز المعاملات المصرفية وسهولة الوصول للموظفين (38.9 %) وهي متوسطة وسرعة الانجاز متوسطة (33.3 %). مستوى الرضا العام للعملاء يميل للحياد أو الرضا النسبي (38.9 %) مما يعكس الحاجة إلى معالجة جوانب الضعف التي تم تحديدها لجلب عملاء جدد. " Abstract: This study aims to highlight the role of investment in modern information technology in developing banking services, through a field study at the Bank of Agriculture and Rural Development, El Oued Agency. To achieve this goal, the descriptive approach was adopted in the theoretical aspect of the study, addressing modern information technology and banking services theoretically. The analytical approach was also adopted in the case study, where interviews and questionnaires were used as the primary tools for the study. The questionnaire was distributed to a sample of the institution's clients. The sample was analyzed using several statistical methods to test the study's hypotheses. A set of results were obtained:  Customers believe that the bank uses modern technology to a moderate to high degree (33.3%(.  The majority of the sample's opinions confirmed that there is room for improvement regarding the speed of completing banking transactions and ease of access to employees (38.9%), which is moderate, and the speed of completion is moderate (33.3%(. The overall customer satisfaction level is neutral or relatively satisfied (38.9%), reflecting the need to address identified weaknesses to attract new customers.
ماستر
Keywords: عربيّــة:الاستثمار; تكنولوجيا المعلومات; الخدمات المصرفية،; بنك الفلاحة والتنمية الريفية; Investment; Information Technology; Banking Services; Bank of Agriculture and Rural Development.